Model Pembelajaran Think Pairs Share (TPS) Sebagai Solusi Untuk Meningkatkan Pemahaman Konsep Matematika Siswa Sekolah Dasar - Desy Alvionita dkk (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Mathematics is a field of study that exists at all levels of education, starting from elementary school, which is the foundation for basic concepts that are used as a basis for learning at the next level. Understanding a concept is very important in the learning process but mathematics is a difficult subject to understand, this is not in accordance with the objectives of learning mathematics, one of which is understanding the concept of mathematics. This writing aims to provide solutions to improve students' conceptual understanding by using the Think Pairs Share (TPS) learning model. The Think Pairs Share (TPS) learning model is a learning process with a pattern of discussion in pairs that are given time to think, respond, and exchange ideas between pairs of the results obtained. The steps of the TPS Model are (a) Thinking. (b) Pairing, (c) Sharing in the implementation of the Think Pair Share (TPS) learning model in the pairing and sharing step, the teacher should encourage students to work together in groups. This writing uses a qualitative approach and the data analysis process puts more emphasis on concluding a comparison of literature reviews from several scientific journals. The results of this study indicate that using the Think Pairs Share (TPS) model can improve students' understanding of mathematical concepts, besides that students are more active in learning so that they can build interest in learning in mathematics learning, and learning outcomes will increase. In using learning models that are more creative, innovative, and paying attention to the characteristics of students and being able to combine learning models with media that are appropriate to the material to be studied so that learning is more interesting, it can be concluded that the Think Pairs Share (TPS) learning model can be used as a solution for improve understanding of elementary school students' mathematical concepts.